2023
DOI: 10.1002/cam4.5811
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L32 enhances hepatocellular carcinoma progression

Abstract: Purpose The underlying mechanisms of hepatocellular carcinoma (HCC) have not been fully investigated, and effective biomarkers for HCC are still needed to be explored. Therefore, our study sought to thoroughly examine the clinical significance and biological functions of the ribosomal protein L32 (RPL32) in HCC by coupling bioinformatic methods with experimental analysis. Methods To determine the clinical significance of RPL32, bioinformatic analyses were performed to examine RPL32 expression in HCC patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… 18 It has been found that RPs are involved in regulating immune cell infiltration in the TME. 19 , 20 Futhermore, a study has demonstrated that RPL22L1 affects the development of lymphocytes. 21 Therefore, it is worth investigating whether RPL22L1 is involved in the regulation of the TME, which in turn influences LUAD progression.…”
Section: Introductionmentioning
confidence: 99%
“… 18 It has been found that RPs are involved in regulating immune cell infiltration in the TME. 19 , 20 Futhermore, a study has demonstrated that RPL22L1 affects the development of lymphocytes. 21 Therefore, it is worth investigating whether RPL22L1 is involved in the regulation of the TME, which in turn influences LUAD progression.…”
Section: Introductionmentioning
confidence: 99%